2008
DOI: 10.1534/genetics.107.084251
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Smoltification-Related Traits in Oncorhynchus mykiss

Abstract: The timing and propensity for migration between fresh-and seawater is a key theme in the diversity of life histories within the salmonid fishes. Across salmonid species, life-history strategies range from wholly freshwater-resident populations, to migratory and nonmigratory variation within populations, to populations and species that are primarily migratory. Despite the central theme of migration to the evolution of these fishes, the genetic architecture of migration-related processes is poorly understood. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
190
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(204 citation statements)
references
References 69 publications
12
190
2
Order By: Relevance
“…Our results provide data from natural populations in California and Oregon that support prior studies on diverse O. mykiss lineages using candidate genes, genome wide association and QTL mapping to explore the genetic architecture of traits associated with life history in O. mykiss, including migration [17,32,42,46,48,[65][66][67][68][69][70][71][72][73][74][75][76]. Many of these studies have identified QTL or significant associations between markers on Omy5 and life-history traits such as spawn timing [47,65,68], smoltification [42,46] and development rate or early maturation [17,66,67,70].…”
Section: Discussionsupporting
confidence: 73%
“…Our results provide data from natural populations in California and Oregon that support prior studies on diverse O. mykiss lineages using candidate genes, genome wide association and QTL mapping to explore the genetic architecture of traits associated with life history in O. mykiss, including migration [17,32,42,46,48,[65][66][67][68][69][70][71][72][73][74][75][76]. Many of these studies have identified QTL or significant associations between markers on Omy5 and life-history traits such as spawn timing [47,65,68], smoltification [42,46] and development rate or early maturation [17,66,67,70].…”
Section: Discussionsupporting
confidence: 73%
“…Quantitative trait loci (QTL) mapping, performed for Oncorhynchus mykiss (Walbaum 1792) (Nichols et al 2008), is also useful in identifying the genomic regions responsible for divergence in behavioral traits and photoperiodic response between migratory and resident forms of G. aculeatus (Fig. 4c).…”
Section: The Future Of Physiological Genomics Of Fish Migrationmentioning
confidence: 99%
“…In rainbow trout, QTL for length after emergence and time to hatching mapped to the same region of the genome, indicating possible pleiotropic effects on size and development rate (Robison et al, 2001;Nichols et al, 2008). Length has been phenotypically correlated with upper thermal tolerance, a physiological trait; two minor QTL for length and thermal tolerance mapped to the same region (Perry et al, 2005).…”
Section: Introductionmentioning
confidence: 98%